Supporting Deterministic Wireless Communications in Industrial IoT - Bartolomeu, Paulo (2020)
Wireless communication technologies have become widely adopted, appearing in heterogeneous applications ranging from tracking victims, responders, and equipment in disaster scenarios to machine health monitoring in networked manufacturing industries. These systems are said to have real-time timeliness requirements since data communication must be conducted within predefined temporal bounds, whose unfulfillment may compromise the correct behavior of the system and cause economic losses or endanger human lives. The support of real-time communications over license-free bands in open environments is a challenging task since real-time medium access is only achieved by a strict timing control of all communicating stations (real and nonreal-time). However, in open communication environments, the traffic generated by uncontrolled stations cannot be avoided by existing medium access protocols. In this paper, the definition, implementation, and assessment of a novel MAC technique named bandjacking is performed. Results demonstrate that the support of low-power deterministic communications is possible in open environments by using bandjacking.